2016
DOI: 10.1002/jmri.25440
|View full text |Cite
|
Sign up to set email alerts
|

Staging liver fibrosis in chronic hepatitis B with T1 relaxation time index on gadoxetic acid‐enhanced MRI: Comparison with aspartate aminotransferase‐to‐platelet ratio index and FIB‐4

Abstract: 4 J. Magn. Reson. Imaging 2017;45:1186-1194.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…A total of 2831 studies were searched by the described search strategies, of which 2627 were excluded following title and abstract screening. Of those, 81 papers were included in the review following full-text screening (Text S5); 47 studies were related to the APRI[24-70], 11 to the ARFI[29,42,69-77], 32 to the FIB-4[24,25,27,30,35,36,39,40,43-46,48-55,57,58,60,62,63,65-69,78-79], 29 to the FibroScan[28,38,42,52,53,58,60,61,71,73,80-98], and 6 to the MRE[99-104].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2831 studies were searched by the described search strategies, of which 2627 were excluded following title and abstract screening. Of those, 81 papers were included in the review following full-text screening (Text S5); 47 studies were related to the APRI[24-70], 11 to the ARFI[29,42,69-77], 32 to the FIB-4[24,25,27,30,35,36,39,40,43-46,48-55,57,58,60,62,63,65-69,78-79], 29 to the FibroScan[28,38,42,52,53,58,60,61,71,73,80-98], and 6 to the MRE[99-104].…”
Section: Resultsmentioning
confidence: 99%
“…Our HeF results were based on clinical patients, which have better reference values than animal experiments, and results for all the fibrosis stages were obtained. Yang et al[ 41 ] used 3D gradient-echo imaging on a 1.5-T MRI scanner to study volumetric interpolated breath-hold examination in liver fibrosis after CHB infection. They found that reduction in T1 relaxation time 20 min after gadoxetic acid injection (ΔT1, ΔR1%) compared with before injection and the contrast uptake rate (K Hep ) decreased significantly as the fibrosis score increased.…”
Section: Discussionmentioning
confidence: 99%
“…More recently published studies have suggested that the gadoxetic acid-enhanced T1 relaxation time index appears to be superior to APRI and FIB-4 for predicting hepatic fibrosis and the combined use of gadoxetic acid-enhanced T1 mapping, APRI, and FIB-4 may be more reliable for staging liver fibrosis in chronic hepatitis B and can be regarded as a useful imaging biomarker of hepatocyte transporter function [144,145]. …”
Section: Mri With Hepatobiliary Contrast Agentsmentioning
confidence: 99%